The Evolution of Prefabrication Based Modular Housing: Expectation and Challenge - Andi asrul Sani (Universitas Bandar Lampung (UBL), 2022)
The building construction industry is on the verge of a massive transformation of construction practices caused by constant pressure to evolve and adapt to increasing global and urban challenges. The neglect of the vernacular building method in the building production process was first realized by using fairly cheap and abundant concrete and reinforced concrete as a substitute for stone and wood, which are the materials of vernacular structures. The world continues to face housing pressures caused by an insufficient inventory of housing units accessible to local residents. This study aims to explore the history of the development of modular-prefabricated construction with a qualitative-histography approach. This goal can be achieved through a series of processes ranging from reviewing relevant literature, discussing findings, and presenting contemporary research themes. The idea of prefabrication was integrated to reinterpret the contemporary sense of dwelling. However, the lack of a concept of knowledge and an understanding of well-defined prefabrications can hinder the integration of methods and theories on the subject. The results of this study show that there is ambiguity regarding the advantages of prefabricated construction practices that are developing today so it becomes a challenge for construction business actors to provide guarantees to the public of the quality of the promised products.